How does research evaluation impact educational research? Exploring intended and unintended consequences of research assessment in the United Kingdom, 1986–2014. (November 2017) - Marques, Marcelo; Powell, Justin JW; Zapp, Mike; Biesta, Gert
Research evaluation systems in many countries aim to improve the quality of higher education. Among the first of such systems, the UK's Research Assessment Exercise (RAE) dating from 1986 is now the Research Excellence Framework (REF). Highly institutionalised, it transforms research to be more accountable. While numerous studies describe the system's effects at different levels, this longitudinal analysis examines the gradual institutionalisation and (un)intended consequences of the system from 1986 to 2014. First, we analyse historically RAE/REF's rationale, formalisation, standardisation, and transparency, framing it as a strong research evaluation system. Second, we locate the multidisciplinary field of education, analysing the submission behaviour (staff, outputs, funding) of departments of education over time to find decreases in the number of academic staff whose research was submitted for peer review assessment; the research article as the preferred publication format; the rise of quantitative analysis; and a high and stable concentration of funding among a small number of departments. Policy instruments invoke varied responses, with such reactivity demonstrated by (1) the increasing submission selectivity in the number of staff whose publications were submitted for peer review as a form of reverse engineering, and (2) the rise of the research article as the preferred output as a self-fulfilling prophecy. The funding concentration demonstrates a largely intended consequence that exacerbates disparities between departments of education. These findings emphasise how research assessment impacts the structural organisation and cognitive development of educational research in the UK.